Pu-erh Tea Extract Ameliorates Ovariectomy-Induced Osteoporosis in Rats and Suppresses Osteoclastogenesis In Vitro - Liu, Titi; Ding, Shihua; Yin, Dan; Cuan, Xiangdan; Xie, Chuanqi; Xu, Huanhuan; Wang, Xuanjun; Sheng, Jun (Frontiers in Pharmacology, 2017)
Background and Objective: Tea drinking is associated with positive effects on bone health and may protect against osteoporosis, especially in elderly women. Pu-erh tea has many beneficial effects on human health; however, whether Pu-erh tea has anti-osteoporotic potential remains unclear. Thus, we investigated the effects of Pu-erh tea extract (PTE) on ovariectomy-induced osteoporosis in rats and on osteoclastogenesis in vitro. Methods: Female Wistar rats were divided into six groups: the sham, model, and Xian-Ling-Gu-Bao capsule (XLGB) groups, and the low-, medium-, and high-dose PTE groups. Ovariectomized (OVX) rats were used as an animal model of osteoporosis. The animals were intragastrically administered distilled water, XLGB, or different concentrations of PTE for 13 weeks. Body weight, blood biochemical indicators, relative organ coefficients, femoral bone mineral density (BMD), bone biomechanical properties, and bone microarchitecture were examined and analyzed. Additionally, the in vitro effects of PTE on osteoclastic activities were investigated using the RAW 264.7 cell line as an osteoclast differentiation model. The effects of PTE on osteoclast differentiation and the expression of osteoclast-specific genes and proteins were determined. Results: PTE reduced OVX-induced body weight gain after 6 weeks of treatment, and the high dose exerted a significant effect. High-dose PTE significantly ameliorated OVX-induced estradiol (E2) deficiency. PTE treatment maintained calcium and phosphorus homeostasis and improved other blood biochemical parameters to various degrees. In addition, PTE treatment improved organ coefficients of the femur, uterus, and vagina and improved femoral BMD and bone biomechanical properties. PTE treatment strikingly ameliorated bone microarchitecture. Moreover, in the in vitro studies, osteoclast differentiation using the differentiation cell model was significantly inhibited by PTE without cytotoxic effects. Additionally, PTE efficaciously suppressed the expression of key osteoclast-specific genes and proteins. Conclusion: PTE can ameliorate ovariectomy-induced osteoporosis in rats and suppress osteoclastogenesis in vitro.